Searching for Sharing Heritage and Multimedia in Africa - Merolla, Daniela; Turin, Mark (World Oral Literature Series, 2017)
"In a world where new technologies are being developed at a dizzying pace, how can we best approach oral genres that represent heritage? Taking an innovative and interdisciplinary approach, this volume explores the idea of sharing as a model to construct and disseminate the knowledge of literary heritage with the people who are represented by and in it. Expert contributors interweave sociological analysis with an appraisal of the transformative impact of technology on literary and cultural production. Does technology restrict, constraining the experience of an oral performance, or does it afford new openings for different aesthetic experiences? Topics explored include the Mara Cultural Heritage Digital Library, the preservation of Ewe heritage material, new eresources for texts in Manding languages, and the possibilities of technauriture. This timely and necessary collection also examines to what extent digital documents can be and have been institutionalised in archives and museums, how digital heritage can remain free from co-option by hegemonic groups, and the roles that exist for community voices. A valuable contribution to a fast-developing field, this book is required reading for scholars and students in the fields of heritage, anthropology, linguistics, history and the emerging disciplines of multi-media documentation and analysis, as well as those working in the field of literature, folklore, and African studies. It is also important reading for museum and archive curators."